Высокотемпературный синтез соединений la 0. 825sr 0. 17mno 3 в порошковом состоянии; Известия вузов. Физика; Т. 57, № 12 - Михайлов М. М.; Власов В. А. Виталий Анатольевич; Утебеков Т. А. Тимур Аскарович; Горпинич Е. В. Екатерина Владимировна (2014, 2014)
Заглавие с экрана